AB0125 Differential Expression of Vascular Inflammation Markers in Collagen-Induced Arthritis and Experimental Atherosclerosis. (9th June 2015) - Denys, A.; Clavel, G.; Lemeiter, D.; Schischmanoff, O.; Assier, E.; Boissier, M.-C.; Semerano, L.
Abstract : Background: Cardiovascular disease (CVD) is a major cause of morbidity and mortality in rheumatoid arthritis (RA). Increased cardiovascular risk in RA is attributed to both traditional risk factors and systemic inflammation over a long period. Limited experimental data exist on vascular involvement in arthritis models 1, 2, 3 . Thus, we developed a model that would mimic both vascular dysfunction and articular inflammation in RA, using collagen-induced arthritis (CIA) in in C57Bl/6 (B6) mice. Objectives: To study the expression of vascular inflammatory markers and atheroma formation in CIA with and without concomitant hyperlipidic diet (HD). Methods: CIA was induced in B6 mice with chicken type-II collagen (cCII) followed by a boost 21 days later. These mice were fed with a standard (chow) diet or with HD given for 12 weeks starting from the day of the boost. The control mice were not immunized (NI) but were fed either the standard diet or HD. Arthritis severity was evaluated using a validated clinical score. Aorta and synovial membranes were removed 15 weeks after the first cCII immunization. We analysed vascular cell adhesion molecule-1 (VCAM-1), inducible NO-synthase (iNOS) and interleukin-17 mRNA level in aorta with real-time quantitative PCR. VCAM-1 localisation in the aortic sinus was determined by immunohistochemistry. In addition, atherosclerotic plaques were assessed in the aorta. Results: CIA was associated with high expression of VCAM-1, independently of the fed diet. VCAM-1 overexpression was detectable 4 weeks after cCII immunization and persisted at 15 weeks. HD induced atheroma plaque formation and aortic iNOS expression which were both independent from CIA. Concomitant CIA and HD had no additive effect on atheroma, VCAM-1 or iNOS expression. Conclusions: In B6 mice, HD and CIA induce distinct and independent expression of large vessel inflammation markers. This model, sensitive to both CIA and experimental atherosclerosis may be relevant for the study of CVD in RA. References: Asquith, D. L., Miller A. M., Hueber A. J., et al. Apolipoprotein E-deficient mice are resistant to the development of collagen-induced arthritis. Arthritis Rheum 2010.62:472-7. Postigo, J., Genre F., Iglesias M., et al. Exacerbation of type II collagen-induced arthritis in apolipoprotein E-deficient mice in association with the expansion of Th1 and Th17 cells. Arthritis Rheum 2011.63:971-80. Rose, S., Eren M., Murphy S., et al. A novel mouse model that develops spontaneous arthritis and is predisposed towards atherosclerosis. Ann Rheum Dis 2013.72:89-95. Disclosure of Interest: None declared